Employment and SMEs during crises - Varum, C.A. (2012)
The persistent increasing duration of unemployment has become an issue during economic crises. Although lay-offs at large firms normally make headlines during crises, we still know little about the potential impact of firm size on adjustment behavior in a crisis. We studied effects of firm size on employment growth during economic slowdowns using a rich microeconomic database for the 1988-2007 period in Portuguese manufacturing industry. The results show that economic downturns affect firm growth negatively. This negative effect is found to be higher for larger firms, both during and immediately following crisis periods. Small and medium-sized enterprises (SMEs) emerge as potential stabilizers in downturn periods. However, larger firms seem to be able to quickly recover from downturn periods. Our results contribute to the scarce literature and to the understanding of the Portuguese case, where many SMEs secure most jobs. These first results may be useful, because SMEs play a determinant role in other European Union economies.